Power factor enhancement for few-layered graphene films by molecular attachments - Sim, Daohao (2012)
In this work, we prepared few-layered graphene (FLG) films and investigated their thermoelectric properties. It was found that pristine FLG films showed a low thermopower of ~40 μV/K. We further processed these FLG films by attaching them with 1,1′-azobis(cyanocyclohexane) or 1,3,6,8-pyrenetetrasulfonic acid. The thermopower of FLG films with attached molecules increased to above ~180 μV/K. Such enhancement in the thermopower led to an increase in their power factor by more than 4.5 times. Theoretical investigation indicated that a potential difference can be introduced between the outer layer and inner layer of FLG films upon molecule attachments. Simulation of the thermopower based on Kubo’s formula provided qualitative support to our experimental results.